Thermoregulation responses in sheep: a cellular approach - Pantoja, Messy Hannear de Andrade (2022)
The overall objective of the study is to characterize the physiological versatility of sheep breed, through thermoregulatory and cellular responses, in biomarkers and morphological and endocrine changes during heat stress. The work was composed of two experiments that were carried out at the Fernando Costa Campus (FZEA) at the University of São Paulo, Brazil. In the first experiment, twenty-four non-pregnant and 18 pregnant Santa Inês ewes (black coat) were used, the animals were evaluated during two consecutive heat waves and in thermoneutrality conditions. During the experiment, weather variables (air temperature, relative humidity and solar radiation), physiological variables (rectal temperature, tympanic temperature and respiratory rate) and hormonal variables (triiodothyronine and prolactin) were recorded. In the second experiment, 80 Santa Inês sheep (black coat) were used, divided randomly in 4 experimental groups (20 animals) housed in paddocks with Aruana grass. Afterwards, each group was kept for seven days in the climatic chamber with a temperature of 36°C (10:00 am to 4:00 pm) and with a reduction of the thermostat to 26 °C from 4:00 pm to 10:00 am. At the end of each cycle, samples were taken of rectal temperature and respiratory rate, ocular surface temperature by infrared thermography and blood for T3 and insulin concentration analysis at 1:00 pm, 4:00 pm, 7:00 pm, 9:00 pm, 1:00 am, 4:00 am, 7:00 am, 10:00 am. Also, skin samples were collected for histological examination in order to evaluate the structure and morphology of the sweat glands. At this moment, microfragments were collected from skin to perform the transcriptome to evaluate the gene expression of possible genes involved in heat tolerance. Physiological parameters were used to select animals high heat tolerant (HHT) and low heat tolerant (LHT), and only these will be evaluated for T3 and insulin concentrations and gene expression. Data analyzed were performed using the statistical program Statistical Analysis System (SAS, 2017). In experiment 1, the physiological variables of pregnant and non-pregnant animals were higher under heat wave conditions and were related to the activation of the thermoregulatory system to maintaining homeothermy. The core body temperature was higher during successive heat waves, as was tympanic temperature, both affected by changes in air temperature. In experiment 2, LHT sheep had higher rectal temperature and right antimere throughout the day. LHT Animals accumulated more heat and needed more time to dissipate excess heat than HHT sheep and finally, 15 genes were found differentially expressed between animals with low and high heat tolerance. The five differentially expressed (DE) genes were upregulated and 10 DE genes were downregulated in the HHT compared with the LHT group. It was possible to identify individuality in relation to thermoregulation capacity and heat tolerance in Santa Inês sheep in the studied group. Further studies are needed to understand how gene regulation behaves in hair sheep.